EFISIENSI ANGGARAN EVALUASI PEMBELAJARAN MELALUI PEMANFAATAN ANDROID BASED TESTING (ABT) DI MI MUHAMMADIYAH AJIBARANG KULON - Muhtar Yusuf (STAI Sufyan Tsauri Majenang, 2020)
This study aims to determine the efficiency of the learning evaluation budget by utilizing Android Bassed Testing (ABT). This research is a descriptive study, a type of research that seeks to describe a phenomenon that exists by describing data in words, and images. The approach in this study is a qualitative approach, namely research that intends to understand the phenomena about what is experienced by research subjects such as behavior, perception, motivation, action and holistically by means of descriptions in the form of words and language, in a special natural context and by utilizing various scientific methods. The results showed that the evaluation of ABT-based learning was very efficient because the madrasa did not need to duplicate the test questions manually, then the ABT also greatly assisted the administration of the teacher, because the teacher did not need to correct student test results.